Higher education leadership : pathways and insights - Ferris, Sharmila Pixy; Waldron, Kathleen (Studies in educational administration (Emerald Group Publishing), 2021)
Offering a unique insider view of higher education, Ferris and Waldron skillfully showcase expert leadership, providing a rich and meaningful understanding of higher education leadership from across the nexus of existential, philosophical and practical concerns.